The dominant factor for mechanical property of polyimide films containing heterocyclic moieties: In‐plane orientation, crystallization, or hydrogen bonding. Issue 39 (21st June 2016) - Luo, Longbo; Zhang, Jing; Huang, Jieyang; Feng, Yan; Peng, Chaorong; Wang, Xu; Liu, Xiangyang
ABSTRACT: Crystallization, in‐plane orientation, and hydrogen bonding interactions are three vital factors for enhancing mechanical properties of polyimide (PI) films. However, which is the dominant factor? In this study, three PI films containing heterocyclic moiety, poly(benzoxazole‐imide), poly(benzimidazole‐imide), and poly(pyrimidine‐imide) were chosen to comparative study. The crystallinity of poly(benzoxazole‐imide), poly(benzimidazole‐imide), and poly(pyrimidine‐imide) PI films are 36, 24, and 15%, respectively. The results of small angle X‐ray scattering indicate poly(benzoxazole‐imide) and poly(benzimidazole‐imide) films show periodical lamellar structures, while poly(pyrimidine‐imide) shows no long period due to low crystallinity. In‐plane orientation ( P 200 ) is calculated from polarized attenuated total reflection (ATR)‐Fourier transform infrared and refractive indices. The order of in‐plane orientation is poly(benzimidazole‐imide) < poly(benzoxazole‐imide) < poly(pyrimidine‐imide). Hydrogen bonding interactions, which restrict chain motion and hinder spontaneous in‐plane orientation, are only formed in poly(benzimidazole‐imide). The relationship between mechanical properties and three influence factors are discussed, and the order of influence extent for mechanical properties of PI films is hydrogen bonding interactions < degree of crystallization < in‐plane orientation. Two structure models for PI films are proposed in order to further confirm the dominant effect of in‐plane orientation on the mechanical properties. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44000. Abstract :